PENGARUH SEDUHAN LEMON TERHADAP INTENSITAS EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI PRAKTEK MANDIRI BIDAN (PMB) WILAYAH KERJA PUSKESMAS BOTANIA - Purba, Netty Herawaty; Julianawati, Tinta; Mariana (Jurnal Ilmiah Kebidanan Imelda, 2023)
Background: Lemon is a source of vitamin C and antioxidants which are beneficial for health. The benefits of lemon are overcoming nausea and vomiting, controlling blood pressure, overcoming digestive disorders, overcoming constipation, increasing endurance, maintaining the bone health of pregnant women and fetuses, a source of antioxidants and others. Pregnancy is a natural process for every woman. One of the inconveniences experienced by pregnant women is nausea and vomiting / emesis gravidarum. This study aims to determine the effect of lemon infusion on the intensity of emesis gravidarum in first trimester pregnant women. Methods: Type of quantitative research with a quasi-experimental research design using a one group pretest-posttest design. The population in this study were all Trimester I Pregnant Women who experienced Emesis Gravidarum in April 2023 totaling 30 people in the PMB Working Area of the Botania Health Center. Sampling using total sampling. The time for the research was April – May 2023 which took place at the PMB working area of the Botania Health Center. The research instrument used the PUQE 24 assessment sheet and was analyzed using Wilcoxon. Results: The results showed that the average emesis gravidarum intensity before being given lemon infusion was 11.03 and the average emesis gravidarum intensity after being given lemon infusion was 7.47. The results of the analysis with a p-value of 0.000 (p <0.05). Conclusion: there is an effect of steeping lemon on the intensity of emesis gravidarum in first trimester pregnant women